Isolated conjunctival lymphoma metastasis from previous low grade non-Hodgkin's lymphoma. Issue 953 (4th March 2005) - Cackett, P; Bower, M; Stebbing, J
Abstract : Ocular involvement of systemic non-Hodgkin's lymphoma is rare. This report describes the unusual occurrence of a biopsy confirmed low grade lymphoma recurring in the conjunctiva, three years after initial diagnosis of systemic disease. The tumour was surgically resected and the patient remains disease free four years later. After the diagnosis of lymphoma, long term follow up is advised as recurrences in unusual sites can occur.